Perkasa Enterprise / Noor Ibrahim Md Isa ... [et al.] - Md. Isa, Noor Ibrahim; Azemi, Nadiah; Aminhamzah, Khairunnisa Afzan; Rosli, Rabbiatul Adawiyah; Abas, Noor Dalila (2003)
Perkasa Enterprise is a company is produce and supply kaolin to the other buyers that used kaolin in their product especially in ceramic manufactured. Kaolin is a clay mineral more correctly knowns as kaolinte. This business operates in No 913, 1st Floor, Lorong Perak 22, Sri Mergong, 05150 Alor Setar, Kedah.